Consideraciones tectosedimentarias sobre la formación Río Diamante, Cordillera de los Andes, Argentina. - Combina, A.M.; Nullo, Francisco (Cuadernos de Geología Ibérica, 1997)
This paper present the stratigrapbie and teetosediníentary relationships of the Río Diamante Formation, which outcrops in Cuchilla de la Tristeza, Cordillera de los Andes, Argentina. The Río Diamante Formation has been originated in a distal aluvial fan environment as a response to Sosneado overthrust. Tectonie deformation related to overthrusting was associated to andesitic volcanism wich influenced the sedimentation. Due to ifie age of overtlirust and volcanies we date the Río Diamante Formation as late Mioeene-early Pliocene. Cuad cojos de Geología 1&rica, núm. 22, 305-320. Servicio de Publicaciones. Universidad Complutense. Maddd, 1997. 306 Ana Al. Combina y Era ncisro Nullo Keys: Tectosedimetation, alluvial fans, thrust, volcanism, Upper Miocene-Lower Pliocene, Cordillera de los Andes.